Cultural Heritage as a Source of Inspiration: Architectural Motifs in Modern Clothing Design - Skaskiv, Olesia; Chuprina, Nataliia (HUDPROM: The Ukrainian Art and Design Journal, 2025)
The article explores the impact of traditional architecture on fashion, focusing on the relationship between architectural forms and clothing design, a dialogue that has persisted throughout history. This connection is evident in both ancient civilizations and modern cultures, reflecting the values, aspirations, and aesthetic preferences of their societies. Examples from Gandhara, Ancient India, the Middle East, and the Mughal Empire illustrate how architectural elements influenced the clothing traditions of those eras. Historical architecture continues to inspire contemporary fashion collections by leading brands. Despite the passage of time and historical epochs, the synergy between architecture and fashion has remained constant, adapting to new contexts. Both disciplines share a symbolic function that contributes to cultural identity and ensures historical continuity. Their interaction fosters mutual enrichment, and for fashion in particular, it opens new ways of rethinking cultural heritage through symbols, proportions, and textures translated into creative design. This is vividly demonstrated through fashion houses and designers: Chloe’s spring-summer 2016 collection, which was inspired by the architecture of the Middle East; Sarah Krainby, in her spring-summer 2024 collection, turns to the heritage of her native Morocco and emphasizes how fragile architectural masterpieces are and how important it is to interpret them in her own collections; Elie Saab’s spring 2024 couture collection was inspired by the intricate patterns inherent in Moroccan architecture. The study underscores the importance of preserving and interpreting the symbolic language of architecture within global culture, especially in the context of increasing efforts to safeguard monuments of national and international significance.